Congenital absence of abdominal muscles: the prune-belly syndrome: a case report - Bahar, Moşe; Özsoylu, Şinasi (The Turkish Journal of Pediatrics, 1968)
A case of congenital absence of abdominal muscles is presented. The patient had bulging abdomen, the lower ribs were flared outwards, and the testes undescended. There were no urinary tract abnormalities. The literature concerning this malformation is briefly reviewed.